Synthesis and Characterization of Chemical Spray Pyrolysed CZTS Thin Films for Solar Cell Applications. (March 2017) - Diwate, Kiran; Mohite, Kakasaheb; Shinde, Manish; Rondiya, Sachin; Pawbake, Amit; Date, Abhijit; Pathan, Habib; Jadkar, Sandesh
Abstract: In present work, thin films of CZTS have been prepared by chemical spray pyrolysis (CSP) by spraying precursor solution directly onto the soda lime glass (SLG) substrates by varying sulphur molar concentration. Copper chloride [CuCl2 .2H2 O], zinc chloride [ZnCl2 .2H2 O], tin chloride [SnCl4 .5H2 O] and thiourea [(NH2 )2 CS] were used as precursor materials to deposit CZTS thin films by using home-built chemical spray pyrolysis system. Influence of sulphur variation on structural, optical, morphology and electrical properties of CZTS films have been investigated by using variety techniques such as low angle x-ray diffraction (XRD), Raman spectroscopy, field emission scanning electron microscopy (FE-SEM), UV-Visible spectroscopy, four probe method, etc. The formation of CZTS has been confirmed by low angle XRD and Raman spectroscopy. The structural analysis reveals formation of kesterite tetragonal phase with preferential orientation along (112) direction. The band gap values of CZTS thin films have been calculated and found in the range 2 - 2.25 eV over the entire range of sulphur variation studied. The change in band gap may be due to quantum confinement effects at nanoscale. The morphological studies show formation of islands of nanoscale particulate clusters which constitute the films in most of the samples. The films exhibit higher resistivity values (in KΩ) which may be due to presence of the strain in the films.